Masjid Kuno di Pulau Haruku Propinsi Maluku (Kajian Sejarah, Bentuk dan Fungsi) - Alfan Firmanto (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
The history of Islamic development on the Haruku island, cannot be separated from the role of Muslim leaders or scholars who came from the Java. Evidence of the influence of Islam in Java can be seen from the architecture of the mosque on this island which takes the form of mosques of Wali in Java. This influence can also be seen from the shape of the terraced roof and floor plan of the mosque is square, which suggests a very strong Javanese mosque architecture. Nevertheless Javanese culture influence on the structure of society in Haruku is not always visible. The mosque on the island Haruku, not only serves as a place of worship, but also has other functions, namely as a symbol of communion between state and customs , as well as a symbol of the existence of an indigenous people. Customary law is a stronger influence than the main sharia law in Rohomoni. This study concludes that the Mosque has developed a more dominant factor as a customary symbol than a religious building. Keywords : Ancient Mosque, Haruku, Ambon, Islam, Indonesia. Sejarah perkembangan agama Islam di pulau Haruku Ambon tidak bisa dilepaskan dari para tokoh ataupun ulama yang berasal dari pulau Jawa. Bukti pengaruh Islam dari Jawa dapat dilihat dari bentuk arsitektur masjid di pulau tersebut yang mengambil bentuk dari masjid-masjid Wali di Jawa. Terlihat dari bentuk Atapnya yang bertumpang dan denah masjid yang berbentuk bujur sangkar, dari segi ini pengaruh arsitektur masjid Jawa sangat kuat. Meskipun demikian secara adat dan budaya tidak terlihat pengaruh budaya Jawa pada struktur masyarakat di Haruku. Masjid di pulau Haruku, tidak sekedar berfungsi sebagai tempat ibadah, tetapi mempunyai fungsi lain yaitu sebagai simbol persekutuan antar negeri dan adat, juga sebagai simbol eksistensi sebuah masyarakat adat. Pengaruh hukum Adat lebih kuat daripada hukum syariat utamanya di negeri Rohomoni. Sehingga terkesan Masjid lebih dominan digunakan sebagai simbol adat daripada bangunan ibadah. Kata Kunci : Masjid Kuno, Haruku, Ambon, Islam, Indonesia.